The Influence of Work Discipline and Work Environment on Job Satisfaction of Operational Employees of CV. Manunggal Jaya Abadi - Wulandari, Puput; Santoso, Bowo (Majapahit Journal of Islamic Finance and Management, 2025)
Job satisfaction is a crucial factor in achieving company goals and maintaining competitiveness. Problems related to work discipline and less than less-than-optimal work environment can negatively affect employee job satisfaction, which ultimately affects company productivity and performance. The purpose of this study was to analyze the effect of work discipline and work environment on the job satisfaction of operational employees of CV. Manunggal Jaya Abadi. This study uses a quantitative approach. Data were collected by distributing questionnaires to 55 operational employees of CV. Manunggal Jaya Abadi uses saturated sampling techniques. Data analysis techniques were carried out using the Partial Least Square (PLS) method. The findings in this study indicate that work discipline and work environment contribute to the job satisfaction of operational employees of CV. Manunggal Jaya Abadi.